PROPHETIC GOOD FATHERING: RESTRUCTURING THE PARENTING PRINCIPLES OF THE PROPHET JACOB IN THE QUR'AN AND HADITH - Syahputri, Agin Mulya; Muna, Arif Chasanul; Fata, Zahrul; Kurniawan, Cecep Soleh (TSAQAFAH, 2025)
This research examines the concept of good fathering in the story of the Prophet Jacob and its contextualization in the concept of modern parenting. This type of research is library research by collecting verses from the Quran and related hadiths, so the method used is theÂ  thematic (maudhu'i) method. The data was analyzed using qualitative content analysis in accordance with the procedures in the maudhu'i interpretation method, namely categorizing the collected data into sub-themes, then structuring and analyzing them. The results of this research are: First, the concept of good fathering contained in the story of the prophet Ya'qub is reflected in his role as a successful father in educating, caring for and accompanying his children who have diverse behavior, and successfully manage problems between siblings. The principles of good fathering that can be taken from the story of the Prophet Jacob are, the function of father as educator (QS 12: 17, 18, 83-87, 94-98), father as protector (QS 12: 4-5, 63-67), father as decision maker (QS 12: 67, 87), father as guardian of harmonious family relationships (QS 12: 17-18, 83-87, 94-98), and father as director of the family vision (QS 12: 38). Second, the concept of good fathering of the Prophet Jacob is very relevant to be contextualized in modern parenting. Prophet Jacob educated his children using a democratic-authoritative parenting model, which prioritizes dialogue with patience and affection. This type of parenting model is very relevant to be applied to raising children amidst the current liberal parenting model in the modern era today.